Aux origines du droit de la radiodiffusion - Stéphane Olivesi (Communication)
The birth of radio broadcasting legislation constitutes a privileged object with which to analyze and understand the genesis of audiovisual communication. Beyond a simple historiographical approach, this article attempt to come to grips with the various social, economic, political and technical stakes involved in the advent of the new medium in the sense that these stakes were reflected upon principally in the normative sense of the law. The laws governing audiovisual broadcasting were designed firstly in response to policing and political needs (maintenance of the public peace, the sovereignty of the State over the ethereal and it’s power in relation to other States, etc.) which have since lessened to the point of disappearing, but which markedly determined both reflection on, and the evolution of, audiovisual media.